A High‐Capacity Cathode for Lithium Batteries Consisting of Porous Microspheres of Highly Amorphized Iron Fluoride Densified from Its Open Parent Phase. Issue 1 (16th August 2012) - Li, Chilin; Mu, Xiaoke; van Aken, Peter A.; Maier, Joachim
Abstract An FeF3 cathode with very high reversible capacity, exceeding 200 mAh g−1, is achieved by amorphizing of FeF3. The amorphization is achieved by densifying the open structure phase along with the removal of channel H2O at 0 °C in BmimBF4. This process is accompanied by a voltage increase of 200 mV. The generation of a hierarchical electron/ion wiring network, enabled by the interaction of ionic liquid with carbon nanotube and FeF3 surfaces, significantly improves the reversibility.